Nikah Sirri dalam Perspektif Hukum Islam, Pancasila, dan Hukum Konstitusi: Menjaga Keadilan Sosial dan Perlindungan Hak Asasi: Sirri Marriage from the Perspective of Islamic Law, Pancasila and Constitutional Law: Maintaining Social Justice and Protection of Human Rights - Ahmad Muhammad Mustain Nasoha; Ashfiya Nur Atqiya; Nabila Nur Aisha; Galuh Sri Lestari; Nur Aulya Rahmah (Litera Academica Publishing, 2024)
The phenomenon of unregistered marriage, or nikah siri, conducted without official state registration, presents challenges in legal and social aspects, particularly regarding inheritance rights, legal protection for wives and children, and equality of rights. This study aims to analyze the perspectives of Islamic law, Pancasila values, and Indonesian constitutional law on unregistered marriages in Indonesia. This research uses normative and conceptual legal approaches, with primary data consisting of relevant laws and secondary data from literature addressing the legal and social dimensions of nikah siri. The results indicate that, from the perspective of Pancasila and the constitution, nikah siri does not align with the principles of social justice and human rights. From the perspective of Islamic law, the importance of marriage registration is also consistent with the objectives of maqasid sharia, which aims to protect family rights. This study recommends educational programs and policy reforms on marriage registration as steps to enhance legal protection and promote social justice within society.